An Intracranial Extradural Dermoid Cyst Presenting with Two Dermal Sinuses and an Abscess in a Child - Aysha Albastaki; Reem AlThawadi; Janan Alajaimi; Khawla F. Ali; Talal Almayman (Case Reports in Neurological Medicine)
Dermoid cysts account for only a small fraction of intracranial masses, with extradural dermoid cysts being considered a much rarer entity than those located intradurally. Intracranial dermoid cysts vary in clinical presentations: some maybe asymptomatic whilst others harbor features of raised intracranial pressure, neurological deficits, or even aseptic meningitis. Dermoid cysts may also present with cutaneous lesions. Herein, we report a rare case of a 1-year-old female presenting with a midline, scalp abscess. Brain MRI revealed an intracranial, extradural tumor, with features suggestive of a dermoid cyst, unusually located in the crista galli, and complicated by the formation of two cutaneous sinus tracts. After identification and characterization by MRI, bitemporal craniotomy was performed with complete excision of the mass and sinus tracts. Histological analysis confirmed dermoid cyst as the final diagnosis. Postoperatively, the patient recovered fully and had no evidence of recurrence in subsequent visits. The case mentioned above highlights the rarity of such a presentation for an intracranial extradural dermoid cyst and the vitality of early imaging for midline cutaneous lesions for identification of intracranial extensions and avoidance of detrimental consequences.